1999
DOI: 10.2519/jospt.1999.29.11.661
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Patellar Taping on Knee Kinetics of Patients With patellofemoral Pain Syndrome

Abstract: conditions. The patellar tape condition did not show a different vertical jump height than the placebo or no-tape conditions. Conclusions: These results suggest that patellar taping compared with no tape may improve the knee extensor moment and power during weight-bearing activities such as the lateral step-up exercise and the vertical jump. / Orthop Sports Phys Ther 1999;29:661-667.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
50
0
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(55 citation statements)
references
References 9 publications
2
50
0
2
Order By: Relevance
“…Studies have found conflicting results depending on the type of subject tested. In those with PFP, improvements in knee flexion angles and knee extensor moments were found with tape 29,30 compared with reductions in knee flexion angles in asymptomatic subjects. 31 In order to better understand the mechanism of action of tape in those with PFP and to remove the confounding effect of pain, we investigated the effect of patellar tape on the EMG onset of the vasti, knee kinematics, and kinetics in individuals with a history of PFP who were currently pain free but had an existing VMO onset timing deficit.…”
Section: Introductionmentioning
confidence: 89%
“…Studies have found conflicting results depending on the type of subject tested. In those with PFP, improvements in knee flexion angles and knee extensor moments were found with tape 29,30 compared with reductions in knee flexion angles in asymptomatic subjects. 31 In order to better understand the mechanism of action of tape in those with PFP and to remove the confounding effect of pain, we investigated the effect of patellar tape on the EMG onset of the vasti, knee kinematics, and kinetics in individuals with a history of PFP who were currently pain free but had an existing VMO onset timing deficit.…”
Section: Introductionmentioning
confidence: 89%
“…The 2 tasks appear to challenge the neuromuscular system in different manners, and both should continue to be used in the investigation of injury risk. J Orthop Sports Phys Ther 2007;37 (5) 18,30,35 While there have been several studies examining electromyographic activity 2,14,38,39,42,43 and sagittal plane knee kinematics and kinetics during the step-down or single-leg squat task, 1,2,7 few studies have examined the frontal and transverse plane kinematics of these tasks. 6,43 A number of studies have investigated lower extremity biomechanics of men and women in an effort to explain the disparity in noncontact ACL injury rates between genders.…”
mentioning
confidence: 99%
“…This method stimulates skin, tendon, and muscle stimulation thus improving joint position sense and proprioception by reducing pain and enhancing recovery of patients. Ernst et al [36] showed that patellar taping on the knee joint improved the alignment of the patella and stability of the knee joints. Also, patella taping produced beneficial effects on balance ability of the knee joint and function of the lower extremity.…”
Section: Discussionmentioning
confidence: 99%